Liberia : 2018 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Liberia. (IMF Staff Country Reports; Country Report ;, 2018)
This 2018 Article IV Consultation highlights that Liberia's economy appears poised for recovery, as growth bottomed out in 2016 and edged to 2.5 percent in 2017. However, Liberia remains fragile with poor living conditions for the majority of the population. Moreover, a decline in aid inflows, which were elevated during 2014-16, has put pressure on the exchange rate and fiscal resources. The government is thus facing the daunting task of pursuing a demanding development agenda in the face of high expectations. Assuming the implementation of sound policies, the medium-term outlook appears favorable. The main upside risk is an increase in commodity prices and output, while downside risks include difficulties in mobilizing resources to fill the financing gap and in pursuing structural and institutional reforms.